Книготорговельна періодика незалежної України (1991–2012) - Gret, Galina (Acta Universitatis Lodziensis. Folia Librorum, 2014)
The role of bookselling periodicals in bookselling of Ukraine is highlighted. It’s formation is considered by visual inspection of magazines „Book”, „New book”, „Soviet bibliophile”, „Biblical news”, which published articles on the history of all branches of books and bookselling also. The articles of newspapers „Form to order”, „Friend reader”, „BETEE”, „Book World”, magazines „Scribe”, „Book Folder” on the period of unconscious publishing support in Ukraine are considered. Materials of magazines „Typography” and „Magazine of the Book Chamber” which are devoted to bookselling on the period of deliberate destruction of Ukrainian books are characterized. The publication of information and analytical magazines such as „Scribe Review”, „Printing & Book”, „Book Review”, „Book Club Plus” which served the book market during the illusion of support of Ukrainian books are analysed. Tendencies of impact of bookselling periodicals on the development of the book market of Ukraine as well as measures of recovery magazines devoted to the book trade are proposed.